THE EFFECT OF EDUCATION ABOUT THE DANGERS OF SMOKING USING LEAFLET MEDIA ON KNOWLEDGE AND ATTITUDES THE HAMLET COMMUNITY OF TANETE LABBA - Jayadi , Yusma Indah; Nurdiyanah; Maharani , Widia (SSD Journal, 2021)
Health education is at achieving goals through behavioral changes that are influenced by several factors, including materials or messages conveyed by teaching aids, methods for health promotion. The purpose of this study was to determine the effect of the use of leaflet media on the knowledge and attitudes of the dangers of smoking in the people of Dusun Tanete Labba, Baji Pa'mai Village, Cenrana District, Maros Regency. Methods This type of research is a quasi-experimental research design with Pretest and Posttest without Control Group Design using leaflet media as a form of education for 30 people. Measurement of knowledge pre-test and post-test using a questionnaire and then analyzed using the T-test to determine and the Wilcoxon test on attitudes. Results The results showed that the use of leaflet media was effective in increasing public knowledge about the dangers of smoking, health education with leaflet media had a significant effect on the level of knowledge p = 0.021 (p < 0.05) and the attitude of respondents p = 0.000 (p < 0.05) related to dangers of smoking. This study concludes that there is an effect of education through leaflets on changes in smoking behavior of the people of Dusun Tanete Labba.